1998
DOI: 10.1016/s0042-6989(97)00340-4
|View full text |Cite
|
Sign up to set email alerts
|

Forced-choice staircases with fixed step sizes: asymptotic and small-sample properties

Abstract: Visual detection and discrimination thresholds are often measured using adaptive staircases, and most studies use transformed (or weighted) up/down methods with fixed step sizes--in the spirit of Wetherill and Levitt (Br J Mathemat Statist Psychol 1965;18:1-10) or Kaernbach (Percept Psychophys 1991;49:227-229)--instead of changing step size at each trial in accordance with best-placement rules--in the spirit of Watson and Pelli (Percept Psychophys 1983;47:87-91). It is generally assumed that a fixed-step-size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
320
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 384 publications
(332 citation statements)
references
References 99 publications
10
320
0
2
Order By: Relevance
“…Secondly, due to the effects of decisional and response bias on the slope and location of the psychometric function in comparative tasks, PSEs or DLs estimated from percent points are contaminated by these influences and do not portray time perception. Finally, and even in the absence of the previous two problems, the most widespread adaptive methods have been shown to provide percent-point estimates that are biased in magnitudes which cannot be assessed without knowledge of the shape of the psychometric function (García-Pérez, 1998, 2000, 2001García-Pérez, 2004, 2007;Faes et al, 2007;Alcalá-Quintana, 2007b, 2009b;Hsu and Chin, 2014). The foregoing discussion does not mean that adaptive methods should be entirely abandoned.…”
Section: Adaptive Methodsmentioning
confidence: 99%
“…Secondly, due to the effects of decisional and response bias on the slope and location of the psychometric function in comparative tasks, PSEs or DLs estimated from percent points are contaminated by these influences and do not portray time perception. Finally, and even in the absence of the previous two problems, the most widespread adaptive methods have been shown to provide percent-point estimates that are biased in magnitudes which cannot be assessed without knowledge of the shape of the psychometric function (García-Pérez, 1998, 2000, 2001García-Pérez, 2004, 2007;Faes et al, 2007;Alcalá-Quintana, 2007b, 2009b;Hsu and Chin, 2014). The foregoing discussion does not mean that adaptive methods should be entirely abandoned.…”
Section: Adaptive Methodsmentioning
confidence: 99%
“…After the second reversal, step size was halved in each direction. This one-up, one-down staircase with unequal step size results in about 78% correct responses (García-Pérez, 1998;Kaernbach, 1991). The staircase was modified so that it never fell below the frame rate of the monitor (13 msec) or above 250 msec.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, in the experimental design of adaptive procedures, forced-choice experiments are often preferred to yes-no paradigms, since they constitute a criterion-free approach to threshold estimation (Kershaw, 1985;Macmillan & Creelman, 1991). For these reasons, two-alternative forced-choice (2AFC) staircases are of widespread use in practical psychophysical experiments (García-Pérez, 1998;Leek, 2001). In up-down staircases, the stimulus intensity for the next trial is increased or decreased upon observing a subset of subject responses, according to a rule that determines the probability of correct response targeted by the procedure (Levitt, 1971;Wetherill & Levitt, 1965).…”
mentioning
confidence: 99%
“…Indeed, the simulation studies of García-Pérez (1998, 2002 have demonstrated that neither the traditionally used transformed and weighted up-down staircases (Kaernbach, 1991;Wetherill & Levitt, 1965) nor some recent modifications of these methods (Kaernbach, 2001a;Zwislocki & Relkin, 2001) yield threshold estimates that correspond to the presumed probability of correct response. More importantly, the simulations in García-Pérez (1998, 2002 showed that unless particular conditions are met, the actual probability that is targeted varies greatly with the relative size of the placed intensity steps with respect to the spread of the underlying psychometric function. These asymptotic and small-sample findings should make 2AFC up-down staircases generally unfit for threshold estimation, since the spread of the psychometric function is an unknown parameter that often varies across subjects and stimuli.…”
mentioning
confidence: 99%
See 1 more Smart Citation